Cipher in the Sand - Bolton, Sandra (Lexington, KY createspace.com, 2011)
Even before the plane touches down in Tegucigalpa, Honduras, Sarah Nelson questions her motives for being there. Murder and romance were not on her list. The year is 1985 and Ronald Regan is president. Following a recent divorce, Sarah joins the Peace Corps. She is assigned to the northern coast of Honduras, a poverty-stricken tropical paradise. The Garifunas, a unique Afro-Amerindian culture, are her nearest neighbors. Her closest ally in times of trouble is the ancient female tribal leader and spiritualist, Xiomara, who draws her into the mysterious world of the supernatural . Sarah's life is forever altered as the naive and idealistic woman encounters more danger and intrigue than she ever bargained for.
Keywords: Fiction; Honduras; Peace Corps